Critical Factors for Field Staff: The Relationship Between Burnout, Coping, and Vocational Purpose. (December 2019) - Kolaski, Alexandra Z.; Taylor, Jennifer M.
Background: Outdoor Behavioral Health Care (OBH) programs rely on field staff (FS) for the daily management of program activities, client safety and security, assessment information, and therapeutic intervention.Purpose: Given research that indicates turnover rates among FS are high, the present study was designed to evaluate components of resilience and burnout among FS that may help OBH programs retain FS.Methodology/Approach: Confirmatory factor analysis was used to empirically examine the impact of McEwan's Workplace Resilience Model factors on FS resilience.Findings/Conclusions: A well-fitting model was developed to explain relationships between burnout, coping skills, and purpose among FS. Important links between vocational purpose, coping, and burnout were found.Implications: This article concludes by discussing implications and recommendations for OBH programs, in support of FS retention and workplace satisfaction, including the importance of creating workplace social and physical health support systems and key characteristics of resilient FS.